Compliance with recommended Varroa destructor treatment regimens improves the survival of honey bee colonies over winter. (May 2022) - Hernandez, Julie; Hattendorf, Jan; Aebi, Alexandre; Dietemann, Vincent
Abstract: The ectoparasitic mite Varroa destructor affects honey bee colony health and survival negatively, thus compelling beekeepers to treat their colonies every year . A broadly used mite control regimen is based on two organic molecules: formic and oxalic acids. To ensure optimal efficiency, several applications of these acids at pre-defined time points are recommended. These recommendations are mainly based on experiments conducted under controlled conditions. Studies evaluating the effectiveness under natural field conditions are lacking. We enrolled 30 beekeepers in a longitudinal study in three cantons in Switzerland and monitored the management and health of their colonies for two years. We assessed compliance with mite control recommendations and measured V. destructor infestation rates, indexes of colony productivity (brood size and honey harvest), and colony mortality in 300 colonies. We observed a 10-fold increased risk of colony death when beekeepers deviated slightly from the recommended treatment regimen compared to compliant beekeepers (odds ratio: 11.9, 95% CI: 2.6–55.2, p  = 0.002). The risk of colony death increased 25-fold in apiaries with substantial deviations from the recommendations (odds ratio: 50.4, 95% CI: 9.7–262.5, p  < 0.0001). The deviations led to increased levels of V. destructor infestation ahead of wintering, which was likely responsible for colony mortality. After communicating the apparent link between low compliance and poor colony survival at the end of the first year to the beekeepers, we observed better compliance and colony survival in the second year. Our results highlight the positive impact of compliance with the recommended V. destructor treatment regimen on the health of honeybee colonies and the need to better communicate the consequences of deviating from the recommendations to improve compliance. Compliance also occasionally decreased, which hints at concept implementation constraints that could be identified and possibly addressed in detail with the help of social sciences to further promote honey bee health. Highlights: We surveyed compliance of beekeepers to Varroa destructor mite control recommendations. Honey bee colony infestation rate and mortality were measured to assess compliance impact. Noncompliance led to higher mite infestation rates and colony mortality. A colony had up to 25 times higher risks of dying when not treated as recommended. Communicating the impact of deviations from recommendations improves compliance.